Peningkatan Kuantitas dan Kualitas Produk pada Perajin Batik Dukuh Kupang Kota Surabaya - Sri Andayani; Endro Tjahyono; Sajio . (JPM17: Jurnal Pengabdian Masyarakat, 2014)
Abstract. The decision moment of batik as world cultural heritage from Indonesia is used maximally by batik craftsmen in the whole Nusantara, unexceptionally batik craftsmen in Surabaya. Surabaya nowadays has had several Batik kampungs in the planning to develop and conserve Surabaya City uniqueness. Prima Amri Surahmat and Suprapti, two batik craftsmen who live at Dukuh Kupang Surabaya area, are partners in the program of IbM 12 persons batik craftsmen group members. Problems of batik making process is too long (not efficient in time) because it must make design /batik motif on paper (Blat) and is moved to cloth one by one, using batik color material from chemical material, makes craftsmen uncomfortable because it is dangerous for health and the sewage can destroy environment. Very traditional entrepreneur management which has no accountancy/entrepreneur noting even though in simple one. The lack of horizon about Marketing Strategy. Execution Method: Methods of training and accompaniment Learning By Doing, and Participative Method. Target and Output :1.Availability of Batik Design Print table to facilitate batik craftsmen in making batik design 2Supplying of Natural Color Matter with raw material from nature.3.Availability of Stainless Steel pan for mordanting process, and Stove and Tube of LPG Gas 4. Increasing of batik tulis production output with natural color. 5.Increasing of entrepreneur management and marketing strategy capabilities, availability of orderly accountancy and entrepreneur activity noting. 6.Availability of Promotion Media in the forms of Brochure and Banner. The achieved output is fit with target and Scientific Bulletin.Keywords: Batik design table, natural color matter, lorot dye tools.